Anthropometric characteristics and traffic accident circumstances of patients with isolated whiplash injury in University Clinical Hospital Mostar - Pejana Rastović; Marija Definis Gojanović; Ines Perić; Marko Pavlović; Josip Lesko; Gordan Galić; Marko Ostojić (Medicinski glasnik, 2017)
Aim: To investigate anthropometric characteristics and traffic accident circumstances of subjects with isolated whiplash injury. Methods: This cross sectional study involved 75 subjects from traffic accidents with isolated whiplash injury classified by Quebec Task Force (QTF). Anthropometric data were collected as well as claims about circumstances of traffic accidents. Results: Distribution of 1 st (28; 37.3%), 2 nd (25; 33.3%) and 3 rd (22; 29.3%) grade of whiplash injury was almost equal. Females had smaller anthropometric measurements than males; neck circumference was the most significant difference between males and females in the context of whiplash injury. The most frequent collision mechanism was impact to front (26; 34.7%) or to rear end (26; 34.7%) of a small passenger's car. Assertions of participants were that their car damage was significant (37; 49.2%) or total (24; 32%). A total of 38 (50.7%) participants claimed that they were not wearing safety belt and 52 (69.3%) did not find themselves responsible for accident. Conclusion: Driving habits of our participants facilitate incidence of whiplash injuries, especially in vulnerable groups such as women and elderly.
Keywords: automobile driver examination; gender identity; claims review